Disseminated Histoplasmosis in Immunocompetent Patients Presented with Fever of Unknown Origin (FUO) (Journal of Medicine, 2023)
Histoplasmosis is underreported although in Southeast Asia including Bangladesh is thought to be endemic considering the favorable geo-climatic conditions for the organism. Non-recognition of histoplasmosis is particularly attributed to possible misdiagnosis as tuberculosis (which is endemic here and common in Bangladesh) because histoplasmosis mimics tuberculosis in clinical presentation, imaging and histopathology. Disseminated histoplasmosis mainly occur in immunocompromised patients and rare in immunocompetent subjects. Here we are reporting two cases of disseminated histoplasmosis where both were immunocompetent and presented with FUO. Both patients visited several health centers before coming to us with no definite diagnosis and we got them in a progressive stage. Both were confirmed through bone marrow study. Unfortunately, one of them died from disease progression, sepsis and other complications and another patient gradually improved with treatment (amphotericin B and itraconazole). We are reporting these cases to highlight the fact that disseminated histoplasmosis does occur in immunocompetent patient and may occur with or without pulmonary symptoms. A high index of suspicion is required for diagnosis and delay can often be fatal.J MEDICINE 2023; 24: 59-64